BER Performance of Optimum Combining with BPSK Modulation in Multipath Fading Environments - Bansal, Rabina (My University, 2007)
Wireless communications is, by any measure, the fastest growing segment of the communications industry. As such, it has captured the attention of the media and the imagination of the public. But, there are many technical challenges that must be overcome in order to make this vision a reality. A signal transmitted on a wireless channel is subject to Fading, Shadowing, Interference, Delay spread, Doppler spread, and Propagation path loss. There is always a greater demand for capacity, reliability and also need to integrate voice, data and other type of traffic over radio channels. There are many ways to solve all these problems, such as Space-time coding, Spread spectrum techniques, Antenna arrays. Diversity techniques are used to mitigate all these above effects. Optimum combining is one of them which is used in space diversity reception is studied in digital cellular mobile radio communication systems with Rayleigh fading, Nakagami fading, & with Ricean fading with multiple cochannel interferers binary phase-shift keying (BPSK) modulation is considered in Rayleigh-fading, Nakagami fading, & with Ricean fading environment when the number of interferences L is no less than the number of antenna elements M (L ≥ M). Exact mathematical framework is also developed to analyze the BER performance of an optimum combining diversity in correlated Nakagami-m channels, Rayleigh fading & with Ricean fading. Simulations are done to find out the BER performance of optimum combining diversity in correlated Nakagami-m channels, Rayleigh fading & with Ricean fading. Simulations are also done to compare BER performance for Multipath fading Environments. It is observed in thesis that for SNR 5dB the combiner in Nakagami fading channel requires 0.1953 BER less as compared to Rayleigh faded channel and 0.0717 BER as compared to Ricean faded channel. Also this thesis includes BER performance for Nakagami Fading with multiple cochannel interferes which is not done previously in any paper.
Keywords: Binary Phase Shift Keying; Rayleigh-Fading; Nakagami Fading; Ricean Fading; Spatial Diversity